Metonymic Target Identification: In Search of a Balanced Approach - Twardzisz, Piotr (Nordic Journal of English Studies, 2014)
The article concerns metonymy observed in certain proper names used in specialist contexts. The names under consideration primarily designate places of international prominence (e.g., the United States, Washington, the White House, Iran, Tehran, etc.). The identification of a metonymic target is the metonymy researcher’s primary goal. The first part of the article reviews and critically assesses several analyses in which authors intuitively search for metonymic targets. In the second part, a passage concerning international relations is scrutinized for the use of the name Iran and other related names. As a whole, the article attempts to demonstrate that metonymic target identification escapes rigorous methodology.